Top Leadership Behaviors Needed by Superintendents in Rural Southwest Missouri Schools - Finney, Joy (Southwest Baptist University, 2019)
Effective school leadership directly and indirectly influences the school setting and teacher and student outcomes (Eliophotou-Menon & Ioannou, 2016). The research of this study examined perceptions of active school teacher’s perceptions of their rural superintendent’s leadership to be effective in southwest Missouri schools. Kent’s (2004) Leadership Behavior Inventory (LBI) was used as the survey instrument and contained five research based transformational leadership behaviors. The inventory was comprised of Likert-type items measuring the perceptions of the teachers and superintendents on the behaviors observed of the rural superintendent. There was a negative to moderately equal relationship between teacher’s perceptions of the five behaviors compared to the superintendent’s perceptions of themselves. Findings of this study support the idea that teacher’s perceptions of superintendent’s behaviors does have an overall effect on superintendent efficacy, staff commitment and retention. If superintendents become knowledgeable of their transformational leadership behaviors and learn to apply them appropriately, superintendents and teachers can demonstrate a symbiotic relationship that leads to the educational organization’s success.